2017
DOI: 10.1002/advs.201700678
|View full text |Cite
|
Sign up to set email alerts
|

Valence State Manipulation of Cerium Oxide Nanoparticles on a Titanium Surface for Modulating Cell Fate and Bone Formation

Abstract: Understanding cell–biomaterial interactions is critical for the control of cell fate for tissue engineering and regenerative medicine. Here, cerium oxide nanoparticles (CeONPs) are applied at different Ce4+/Ce3+ ratios (i.e., 0.46, 1.23, and 3.23) to titanium substrate surfaces by magnetron sputtering and vacuum annealing. Evaluation of the cytotoxicity of the modified surface to cultured rat bone marrow mesenchymal stem cells (BMSCs) reveals that the cytocompatibility and cell proliferation are proportional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 73 publications
2
105
0
Order By: Relevance
“…For instance, alkali‐treatment coating could be used as a scaffold to allow for the sustainable release of the therapeutic agents, particularly inorganic bioactive elements such as Sr, and other trace elements. However, these studies rendered multifunctional surfaces by loading different factors into single release system . Such single release system released different agents simultaneously and independent release program was not shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, alkali‐treatment coating could be used as a scaffold to allow for the sustainable release of the therapeutic agents, particularly inorganic bioactive elements such as Sr, and other trace elements. However, these studies rendered multifunctional surfaces by loading different factors into single release system . Such single release system released different agents simultaneously and independent release program was not shown.…”
Section: Discussionmentioning
confidence: 99%
“…The following biological behaviors could therefore be regulated through cell recruitment, antigen presentation, and immunoregulation . It has been proved that macrophages are vital to the initial tissue healing process . Sun et al reported the positive function of osteo macrophages in skeletal remodeling .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in M2 percentage could increase the production of anti-inflammatory cytokines. 128 Also, the high Ce 4+ presented a higher catalase activity, but a lower peroxidase activity. Results of protein adsorption and conformation indicated that the exposed cell-binding sites of fibronectin and subsequent cell morphology were associated with the Ce valence state.…”
Section: Cerium Oxide Coating For Titanium-based Implantsmentioning
confidence: 90%
“…More recently, CeO 2 NPs incorporated into hydroxyapatite coating, via the plasma spraying technique, induced polarization of murine RAW264.7 macrophages towards the M2 phenotype, as demonstrated by the upregulation of the M2 surface markers CD163 and CD206, promoting an osteogenic behavior of bone mesenchymal stem cells (BMSCs) [ 53 ]. The improved osteogenic differentiation ability of BMSCs was further found to be proportional to the surface Ce 4+ /Ce 3+ ratio; indeed, the higher ratio achieved better osseointegration in vivo, and enhanced murine macrophages polarization towards the M2 phenotype, increasing the levels of anti-inflammatory cytokines [ 54 ].…”
Section: Nanoparticles To Direct Macrophage Polarizationmentioning
confidence: 99%